DETERMINANTS OF NON PERFORMING FINANCING (NPF) ON SHARIA RURAL BANKS (BPRS) IN INDONESIA - Muhammad, Muhammad (Efficient: Indonesian Journal of Development Economics, 2019)
The purpose of this research is to find out and analyze the determinants of NPF on BPRS in Indonesia in 2011 -2017. The method which is used in this study is a multiple linear regression analysis with independent variables CAR, BPP, inflation, and GDP, while the dependent variable is NPF. The data in this study is secondary data for monthly time from January 2011 - December 2017. The results showed that the independent variables significantly influence NPF simultaneously. While partially CAR has a significant positive effect, BPP has a significant negative effect, inflation has no significant positive effect, and GDP has a significant positive effect on NPF. R2 value is 88.01%, this shows 88.01% variation of the NPF is explained by the independent variable and the remaining 11.99% is explained by other variables outside the model. BPRS needs to carry out good risk management by having to be more sensitive to internal conditions and external conditions of the bank because these conditions can be used as determinants of the type of financing and policies that will be used by the BPRS, so as to control the level of NPF at a reasonable level. Tujuan dari penelitian ini adalah untuk mengetahui dan menganalisis factor penentu NPF pada BPRS di Indonesia padatahun 2011-2017. Metode yang digunakan dalam penelitian ini adalah analisis regresi linier berganda dengan variable bebas CAR, BPP, inflasi, dan PDB, sedangkan variable terikatnya adalah NPF. Data dalam penelitian ini adalah data sekunder untuk waktu bulanan dariJanuari 2011 - Desember 2017. Hasilpenelitian menunjukkan bahwa variable independen secara signifikan mempengaruhi NPF secara bersamaa Sementara sebagian CAR memiliki efek positif yang signifikan, BPP memiliki efek negatif yang signifikan, inflasi tidak memiliki efek positif yang signifikan, dan PDB memilikiefekpositif yang signifikanterhadap NPF. Nilai R2 adalah 88,01%, inimenunjukkanvariasi NPF 88,01% dijelaskan oleh variable independen dan sisanya 11,99% dijelaskan oleh variabel lain di luar model. BPRS perlu melakukan manajemen risiko yang baik dengan harus lebih peka terhadap kondisi internal dan kondisi eksternal bank karena kondisi ini dapat digunakan sebagai penentu jenis pembiayaan dan kebijakan yang akan digunakan oleh BPRS, sehingga dapat mengendalikan tingkat NPF pada tingkat yang wajar.